EVALUASI PENERAPAN TRANSFER PRICING DI PERUSAHAAN MANUFAKTUR : STUDI KASUS DI INDONESIA (Media Riset Akuntansi, 2022)
This research attempts to analyze the tax treatment to transfer pricing transactions in the manufacturing company in Indonesia. Qualitative research methods that were used is descriptive. Data were collected by doing research content analysis and study documentation. The result of this research indicated that the company which is pointed out doing transfer pricing in Indonesia involved to loss in revenue from local taxes, this is because of the differences in tax rates among countries and make the company looking for a crack to gain advantage. Due to differences in tax rates have led to some companies that is suspected of commiting transfer pricing having a special relationship with the countries with a low tax rates.